(untitled) (Research, Society and Development, 2022)
Introduction: the emergence of electronic games took place in the 70s, with the passage of time and its constant improvements became a phenomenon in the cultural industry, reaching billions of dollars and being a reason for discussion in public health. Objective: to identify characteristics and observe the intensity of somatic, cognitive anxiety and self-confidence of e-Sports players moments before matches. Methodology: initially, electronic messages were sent via social network to 53 teams participating in national competitions, to present the study and make the invitation. The invitation consisted of answering three questionnaires, the IPAQ, the CSAI-2R and a questionnaire to characterize the sample, minutes before entering an official game competition, both on an online platform through Microsoft Forms. In the questionnaires there were questions about aspects correlated to the health and level of anxiety and self-confidence of the players in the pre-competition period. Result: the average age of the players was 20.93 ± 1.85 years, cognitive anxiety was present with a mean of 21.83 ± 8.12 and somatic 17.07 ± 5.32, being considered the average level. -dio of specialization in the current sport for players 49.4 %, still, presented indices of sedentary lifestyle 51.9 %. Conclusion: the vast majority of athletes are young, and consider themselves to be of medium level in the sport in question. Subjects showed medium levels of cognitive anxiety, even with self-confidence present, and low levels of somatic anxiety before competitions.